The design of artificial grafts using multi-objective genetic algorithms - C. F. Castro (2012)
The geometry configuration of vascular bypass grafts has profound influence on the physiologic flow pattern. Poor geometries might be correlated with postoperative occlusion pathogenesis. Improving the blood flow dynamics in the bypass is an important element for the long-term success of bypass surgeries. Genetic algorithms are effective tools to identify optimal shapes of grafts given a robust fluid dynamics numerical solver able to determine the main flow features of different setups. This paper focuses on a specific graft shape and three design variables: graft calibre, graft angulation and suture sizing. A multi-objective shape optimization algorithm considers a genetic algorithm iterating over numerically simulated flow through idealized bypass grafts. Shape optimization is accomplished by simultaneously minimizing shear stress and recirculation zones. (c) Civil-Comp Press, 2012.